An integrated microfluidic flow-focusing platform for on-chip fabrication and filtration of cell-laden microgels. Issue 9 (21st March 2019) - Mohamed, Mohamed G. A.; Kheiri, Sina; Islam, Saidul; Kumar, Hitendra; Yang, Annie; Kim, Keekyoung
Abstract : An integrated microfluidic flow-focusing platform for on-chip fabrication and filtration of cell-laden microgels. Abstract : We present the development of a stable continuous, and integrated microfluidic platform for the high-throughput fabrication of monodisperse cell-laden microgel droplets with high and maintained cellular viability. This is through combining onto one chip all the required processes from the droplet generation in a flow focusing microfluidic junction passing through on-chip photocrosslinking to the separation of the droplets from the continuous oil phase. To avoid cellular aggregation during the droplet generation process, cells were treated with bovine serum albumin (BSA) before mixing with gelatin methacrylate (GelMA). And, a magnetic mixer was applied to the GelMA prepolymer-cell suspension syringe to eliminate cell sedimentation. These approaches resulted in having a reasonable distribution of cells among monodisperse microdroplets. The microdroplets were irradiated with a 405 nm wavelength laser beam while passing through the crosslinking chamber of the microfluidic device. The produced microgels enter the filtration unit of the same device where they were gently separated from the oil phase into the washing buffer aqueous solution of Tween 80 using the filter microposts array. The viability of the encapsulated cells was around 85% at day 1 and was maintained throughout 5 days. Using this method of controlling cell encapsulation with on-chip crosslinking and oil filtration, highly efficient cell-laden microgel production is achieved. The presented integrated microfluidic platform can be a candidate for standard cell-encapsulation experiments and other tissue engineering applications.